Involvement of DNA Repair Genes and System of Radiation-Induced Activation of Transposons in Formation of Transgenerational Effects - Yushkova, Elena (Frontiers in Genetics, 2020)
The study of the genetic basis of the manifestation of radiation-induced effects and their transgenerational inheritance makes it possible to identify the mechanisms of adaptation and possible effective strategies for the survival of organisms in response to chronic radioactive stress. One persistent hypothesis is that the activation of certain genes involved in cellular defense is a specific response of the cell to irradiation. There is also data indicating the important role of transposable elements in the formation of radiosensitivity/radioresistance of biological systems. In this work, we studied the interaction of the systems of hobo transposon activity and DNA repair in the cell under conditions of chronic low-dose irradiation and its participation in the inheritance of radiation-induced transgenerational instability in Drosophila. Our results showed a significant increase of sterility and locus-specific mutability, a decrease of survival, fertility and genome stability (an increase the frequency of dominant lethal mutations and DNA damage) in non-irradiated F1/F2 offspring of irradiated parents with dysfunction of the mus304 gene which is responsible for excision and post-replicative recombination repair and repair of double-stranded DNA breaks. The combined action dysfunction of the mus309 gene and transpositional activity of hobo elements also led to the transgenerational effects of irradiation but only in the F1 offspring. Dysfunction of the genes of other DNA repair systems (mus101 and mus210) showed no visible effects inherited from irradiated parents subjected to hobo transpositions. The mei-41 gene showed specificity in this type of interaction, which consists in its higher efficiency in sensing events induced by transpositional activity rather than irradiation.